Pengaruh Pertumbuhan Penjualan dan Devidend Terhadap Harga Saham - Muh Syahrul Sa'ban; Aris Munandar (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
The purpose of this study is to determine the extent of the effect of sales growth and dividends on the stock price of PT. Gudang Garam, Tbk for the period 2014-2018. The stock price is a reflection of the condition of a company where the price of shares that occur on the stock market at a certain time. High stock prices will provide returns for investors in the form of capital gains which will ultimately affect the company's image. This research is categorized into the type of causal research with quantitative methods. The population in this study is the entire company data for the period 1971-2018 with the number of research samples of 5 years, namely 2014-2018. The sampling technique uses purposive sampling method. Data source is secondary data. Data analysis tools use the classic assumption test, multiple linear regression and hypothesis testing. From the results of the study note that partially and simultaneously sales growth and dividends have a positive impact on the stock price of PT. Gudang Garam, Tbk.